Pengelolaan Perkebunan Berkelanjutan yang Berkearifan Lokal di Lahan Basah - Partini; Noer, Melinda; Suliansyah, Irfan; Devianto, Dodi (Jurnal Galung Tropika, 2024)
Wetlands are essential in economic and ecological systems, especially in tropical regions. Economically, this land has the potential to be used for agriculture, fishery plantations, and animal husbandry. Ecologically, wetlands are ecosystems that are rich in biodiversity and function as carbon sinks, natural water filters, and providers of natural resources for surrounding communities. The management approach must involve not only modern technology but also local wisdom to realize sustainable plantations in wetlands. Local practices in wetland management that support sustainable plantations include local knowledge in choosing adaptive commodities, fire prevention, agroforestry systems, togetherness in society, rituals, traditions and community beliefs, cooperation in communities, and customary law. The wisdom values contained in this practice include respect for the environment, collaboration within the community, preservation of heritage and culture, adaptability and resistance to change, spiritual values, and respect for ancestors.